2022
DOI: 10.3390/ani12101224
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Characteristics of Farms That Raise Pigs without Antibiotics

Abstract: Reduced and responsible antimicrobial use leads to a lower risk of developing antimicrobial resistance. Raised Without Antibiotics (RWA) is a certification label that is recognized in only a few countries, and it is often unclear what the specific criteria and characteristics of RWA farms are. The objectives of this study were to describe the criteria for a Belgian RWA program; to coach farms towards reduced antimicrobial usage (AMU); to assess if it was possible to obtain and maintain the RWA status; and to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The impact of the awareness campaigns (or coaching) and the economic benefits of farm biosecurity interventions in curbing AMU has been assessed in several studies [29][30][31]44]. In a study on Dutch dairy herds, a combination of awareness-raising and restrictive measures was found to reduce antibiotic use by 17% in 2012 compared to 2009 [44].…”
Section: Farm Biosecurity (Or Management) Factors Affecting Antimicro...mentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of the awareness campaigns (or coaching) and the economic benefits of farm biosecurity interventions in curbing AMU has been assessed in several studies [29][30][31]44]. In a study on Dutch dairy herds, a combination of awareness-raising and restrictive measures was found to reduce antibiotic use by 17% in 2012 compared to 2009 [44].…”
Section: Farm Biosecurity (Or Management) Factors Affecting Antimicro...mentioning
confidence: 99%
“…In a study on Dutch dairy herds, a combination of awareness-raising and restrictive measures was found to reduce antibiotic use by 17% in 2012 compared to 2009 [44]. Another study on raising pigs without antibiotics (RWA) reported that farmers could achieve and maintain RWA status through farm-specific coaching related to prudent AMU and improved biosecurity [29]. A study on pig farms found that implementing new biosecurity measures and vaccinations led to an increase in enterprise profit of +€2.67/finisher pig/year [30].…”
Section: Farm Biosecurity (Or Management) Factors Affecting Antimicro...mentioning
confidence: 99%
“…However, specific inclusion criteria for RWA production and the implementation of RWA in a large number of herds with varying management and housing conditions has only been limitedly investigated. In a recent Belgian study [ 61 ], 28 Belgian pig herds were enrolled, and their ABU was followed for a period of 35 months. The goal of the study was to evaluate to what extent pig farms could be coached towards antimicrobial-free pig production and to what extent they could also maintain this status over time.…”
Section: Antimicrobial Use In Pig Production In Europe: the Way Forwardmentioning
confidence: 99%